Pharmacological cardioversion of recent-onset atrial fibrillation in patients with chronic kidney disease: sub-analysis of the CANT study. (14th October 2021) - Ceynowa-Sielawko, B; Wybraniec, M; Topp-Zielinska, A; Maciag, A; Miskowiec, D; Krzowski, B; Balsam, P; Wojcik, M; Wrobel, W; Farkowski, M; Kozinski, M; Kasprzak, J; et al.
Abstract: Purpose: Pharmacological cardioversion (PCV) is commonly a primary option for termination of recent-onset atrial fibrillation (AF) at the emergency departments (ED), and there are reports proving that antazoline is a noteworthy agent to restore sinus rhythm. This is a sub-analysis of the CANT study evaluating the effectiveness and safety of antazoline in patients with AF at different stages of chronic kidney disease (CKD). Methods: Total n=777 patients admitted to ED for the urgent termination of AF were included into this analysis. We analysed the results concerning effectiveness and safety of PCV with special consideration of antazoline, in patients at 3 stages of CKD defined on the basis of eGFR (CKD-EPI): Group I ≥60 mL/min (n=531), Group II 45–59 mL/min (n=149), and Group III <45 mL/min (n=97). Primary end-point was the termination of AF, a restoration of a sinus rhythm and its persistence until discharge. Results: Patients of group III were older and with higher prevalence of comorbidities, however, we have not found statistically significant differences in overall effectiveness of PCV in comparison with the other groups. In patients receiving amiodarone, the PCV success rate was similar in all the studied groups, but along with a renal function decline, it decreased in patients receiving antazoline (79.1 vs 35%; p<0.001), and it increased close to a significant manner in patients receiving propafenone (69.9 vs 100%; p=0.067; Figure). In patients of Group I, antazoline restored a sinus rhythm as effectively as propafenone and amiodarone, however in patients of Group III, both antazoline and amiodarone became less effective in restoring a sinus rhythm than propafenone (p=0.002 and p=0.034, respectively). The rate of safety endpoint was highest in patients of Group III (eGFR<45 mL/min), and it was significantly higher than in patients of Group I and II (p=0.008 and p=0.036, respectively). We have not observed antazoline-related adverse events in any of studied groups of patients. Conclusion: This real-world registry analysis revealed a different influence of CKD on individual drug effectiveness, and while propafenone and amiodarone maintained their AF termination efficacy, antazoline became significantly less effective in restoring sinus rhythm. Its favourable safety profile has not changed. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The study received no external funding